Eliminating indirect energy subsidies in Ukraine: Estimation of environmental and socioeconomic effects using input-output modeling - Iuliia Ogarenko; Klaus Hubacek (Journal of Economic Structures, 2013)
Energy subsidies are causing adverse effects on the economy and environment stimulating inefficient resource allocation and excessive energy consumption. Therefore, multiple positive effects are likely to be obtained if subsidies are reduced or removed completely. This study estimates indirect end-user energy subsidies in gas and electricity sectors of Ukraine and assesses short-term environmental and socioeconomic effects of a hypothetical elimination of these subsidies. Consumer subsidies are quantified utilizing the price-gap approach that compares end-user prices and reference prices that would predominate in competitive markets where no subsidies are provided. Input-output analysis is undertaken to investigate impacts in the short-term. First, a price model is utilized to estimate price changes resulting from subsidy elimination and then a demand-driven IO model is adopted for estimation of associated changes of environmental and social variables. As a result of elimination of energy subsidies, total energy consumption and GHG emissions would decline by about 2.5 % and 3.6 %, respectively. In addition, distributional effects of a subsidy reform are analyzed utilizing data on consumption patterns of different income groups.
Keywords: D57; P22; P28; Q41; 330; Energy subsidies; Input-output modeling; Price-gap approach; Ukraine; CO2